2014
DOI: 10.1242/jeb.109355
|View full text |Cite
|
Sign up to set email alerts
|

Planar covariation of limb elevation angles during bipedal locomotion in common quails (Coturnix coturnix)

Abstract: In human bipedal walking, temporal changes in the elevation angle of the thigh, shank and foot segments covary to form a regular loop within a single plane in three-dimensional space. In this study, we quantified the planar covariation of limb elevation angles during bipedal locomotion in common quails to test whether the degree of planarity and the orientation of the covariance plane differ between birds, humans and Japanese macaques as reported in published accounts. Five quails locomoted on a treadmill and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…During forward progression, HL and FL segments oscillate back and forth with specific phasing relative to the footfall pattern ( Figure 3A ). We confirmed the validity of the planar covariation previously reported in humans ( Bianchi et al, 1998b ), macaques ( Courtine et al, 2005 ; Ogihara et al, 2012 ), birds (quails, Ogihara et al, 2014 ), and dogs ( Catavitello et al, 2015 ), and extended it to a large set of other animal species. Even though different recording systems were used in these previous studies, the planarity index (PV 3 ~1–3%) and the orientation of the covariation plane ( u 3 vector) for the bird ( Ogihara et al, 2014 ), human ( Bianchi et al, 1998a ) and dog ( Catavitello et al, 2015 ) were similar to those reported in the current study ( Figure 3 ), confirming the reliability of our kinematic recordings and suggesting that each animal adopted its own pattern of the inter-segmental coordination.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…During forward progression, HL and FL segments oscillate back and forth with specific phasing relative to the footfall pattern ( Figure 3A ). We confirmed the validity of the planar covariation previously reported in humans ( Bianchi et al, 1998b ), macaques ( Courtine et al, 2005 ; Ogihara et al, 2012 ), birds (quails, Ogihara et al, 2014 ), and dogs ( Catavitello et al, 2015 ), and extended it to a large set of other animal species. Even though different recording systems were used in these previous studies, the planarity index (PV 3 ~1–3%) and the orientation of the covariation plane ( u 3 vector) for the bird ( Ogihara et al, 2014 ), human ( Bianchi et al, 1998a ) and dog ( Catavitello et al, 2015 ) were similar to those reported in the current study ( Figure 3 ), confirming the reliability of our kinematic recordings and suggesting that each animal adopted its own pattern of the inter-segmental coordination.…”
Section: Discussionsupporting
confidence: 87%
“…we found that the u 3 vector rotation correlated with L shank /L foot and L thigh /L foot ), the orientation of the covariation plane reflects specific phase relationships in the control of segment motions ( Bianchi et al, 1998b ; Lacquaniti et al, 2002 ; Ivanenko et al, 2008 ). For instance, birds form a group of animals with a compact orientation of the u 3 vector close to the thigh axis ( Figure 4A , see also Ogihara et al, 2014 ) while primates show rather variable u 3 orientation ( Figure 3—figure supplement 1 ). Also, birds show characteristically wide gait loops, while for other animals the loops are much narrower for HL ( Figure 3—figure supplement 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have found evidence of joint coordination in steady locomotion (e.g. Ogihara et al, 2014), and we identified similar integration of hip and knee LAR during maneuvering (Kambic et al, 2014). However, in this study we did not find a strong correlation between hip and knee LAR patterns -a result that should be investigated further.…”
Section: Implications and Future Workcontrasting
confidence: 77%
“…Fischer et al, 2002;Stoessel and Fischer, 2012) that are typically unique and not transferrable between species with different leg geometries (Gatesy and Pollard, 2011). This suggests the existence of criteria such as simplification of locomotor control (Ogihara et al, 2014) or economy of locomotion (Alexander, 1991;Günther et al, 2004) that govern the motion of the segments.…”
Section: Introductionmentioning
confidence: 99%